Identificação de padrões de metadados para preservação digital - Formenton, Danilo (2015)
With the significant increase in the production and acquisition of digital content, initiatives for the recovery and long-term data preservation are being created and studied in the light of changes in technological storage and access to information resources. In this context, the aim of the research was to verify to what extent standards or metadata schemas for digital preservation have been discussed by the field of Information Science and related fields (Archival Science, Library Science, Museology etc.), pointing out how these schemas could meet the structuring demands of institutional repositories more adequately for the preservation of digital documents. In terms of method, an exploratory study, based on bibliographic and documentary research relating to standards or metadata schemes used in the scope of digital preservation, was conducted. A comparative analysis of standards or metadata schemes identified in the literature was carried out, based on core metadata elements considered for digital preservation. Regarding the results, a theoretical technical framework is presented, that seeks to systematize standards or metadata schemes applicable to digital preservation, such as DC, MODS, EAD, ANSI/NISO Z39.87 or MIX, METS and PREMIS and at the same time, that may be relevant for modeling digital institutional repositories. It was found that the guarantee of long-term digital preservation will only be possible with the effective implementation of standards and metadata schemas, because it is they that define the description, representation, consistency and persistence of the digital object/resource in the information environment, as well as determining interoperability between systems. There is no way to say which of the existing metadata schema fully ensures digital preservation but that it is indeed possible to have different standards working together in order to complement the effective registration of the information required in managing preservation and usable access over time of digital objects/resources.